PENGUASAAN PEMBELAJARAN BAHASA ARAB SISWA KELAS VII TERHADAP PEMBELAJARAN DARING PADA MADRASAH YTSANAWIYAH AL HASANAH SLAHUNG PONOROGO - Sri ana; Samsul Mukani (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
: Learning is a teaching activity carried out maximally by a teacher so that the students he teaches certain materials carry out learning activities well. In other words, learning is the effort made by the teacher in creating certain material learning activities that are conducive to achieving goals in the process of learning activities. This study aims to determine (1) the Arabic language mastery ability of the seventh grade students of MTs Al Hsanah Slahung Ponorogo (2) the results of the application of online Arabic learning in class VII MTs Tsanawiyah Al Hasanah Slahung Ponorogo (3) The results of online Arabic learning on mastery Arabic language for seventh grade students of MTs Al Hasanah Slahung Ponorogo. This thesis research uses mixed methods research. With data collection methods in the form of interviews, observations, documentation and questionnaires. The data collected is related to